The role of illness perception and emotions on quality of life in fibromyalgia compared with other chronic pain conditions The role of illness perception and emotions on quality of life in fibromyalgia compared with other chronic pain conditions - E. Sgnaolin; P. De Sandre; M. Podswiadek; M. Dalla Valle; M. Capraro; R. Ferrari (PAGEPress Publications, 2012)
Objective: Fibromyalgia syndrome (FMs) is a chronic widespread pain condition that can negatively impact on all aspects of patient's life. The purpose of this study was: first, to evaluate illness perception (IP), quality of life (QoL) and affective-emotive variables (EAV) of patients with FM; and second, to compare these variables to different pain conditions. Methods: Consecutive 34 women (mean age 47.4±8.3 years) affected by FM were enrolled for the study from December 2009 to May 2011. IP was evaluated by means of the Revised Illness Perception Questionnaire, QoL through Nottigham Health Profile and EAV through the Beck Depression Inventory. Scores were compared with rheumatoid arthritis (RA) (n=20; mean age 53±12.8 years) and low back pain (LBP) (n=20; 51.3±7.8 years) groups. Results: FM patients scored higher than RA and LBP groups on IP (Identity scale mean: FM=8.8±2.3, AR=5.5±3.3, LBP=4.1±2.9; Kruskal-Wallis=24.42). Moreover FM patients show higher EAV (mean FM=21±9.6, AR=8.9±5.6, LBP=14.9±6.5; Kolmogorov-Smirnov Z=2.17) and QoL (Pain scale mean: FM=74.2±24.1; AR=35.7±19.9; LBP=56.5±20.4; Kolmogorov-Smirnov Z=2.27; Energy scale mean: FM=86.2±28.5; AR=46.8±35.4; LBP=61.6 ±63.7; Kolmogorov-Smirnov Z=1.98) than RA group. Conclusions: Our study highlighted dysfunctional IP, low QoL, high EAV scores in FM patients and the significant relations between these variables. Research results provided support for relevance of a multidisciplinary approach to the management of FM, including psychological interventions, according to a biopsychosocial perspective. Objective: Fibromyalgia syndrome (FMs) is a chronic widespread pain condition that can negatively impact on all aspects of patient's life. The purposes of this study were: i) to evaluate illness perception (IP), quality of life (QoL) and affective-emotive variables (EAV) of patients with FM; and ii) to compare these variables to different pain conditions. Methods: Consecutive 34 women (mean age 47.4±.8.3 years) affected by FM were enrolled for the study from December 2009 to May 2011. IP was evaluated by means of the Revised Illness Perception Questionnaire, QoL through Nottigham Health Profile and EAV through the Beck Depression Inventory. Scores were compared with rheumatoid arthritis (RA) (n=20; mean age 53±12.8 years) and low back pain (LBP) (n=20; 51.3±7.8 years) groups. Results: FM patients scored higher than RA and LBP groups on IP (Identity scale mean: FM=8.8±2.3, AR=5.5±3.3, LBP=4.1±2.9; Kruskal-Wallis=24.42). Moreover FM patients show higher EAV (mean FM=21±9.6, AR=8.9±5.6, LBP=14.9±6.5; Kolmogorov-Smirnov Z=2.17) and lower QoL (Pain scale mean: FM=74.2 ±24.1; AR:35.7±19.9; LBP:56.5±20.4; Kolmogorov-Smirnov Z=2.27; Energy scale mean: FM=86.2±28.5; AR=46.8±35.4; LBP=61.6±63.7; Kolmogorov-Smirnov Z=1.98) than RA group. Conclusion: Our study highlighted dysfunctional IP, low QoL, high EAV scores in FM patients and the significant relations between these variables. Research results provided support for relevance of a multidisciplinary approach to the management of FM, including psychological interventions, according to a biopsychosocial perspective.